The European Court of Human Rights and the myth of freedom of religion - Vargiu, Paolo (Il diritto ecclesiastico, 2024)
The European Court of Human Rights (ecthr) plays a vital role in safeguarding religious freedom amid rising extremism and intolerance in Europe. This article argues that the Court acts not only as a legal body but also as a cultural mediator, shaping a pluralistic ethos through its jurisprudence. Using Roland Barthes’ concept of myth, the article explores how ecthr case-law reflects Europe’s historical, social, and political narratives, balancing universal rights with national traditions. The Court has moved from prioritizing dominant cultural paradigms to embracing multiculturalism, promoting a pluralistic model that integrates diverse beliefs while rejecting rigid neutrality. Interpreting Article 9 inclusively, the ecthr protects cultural diversity, combats fundamentalism, and promotes a European pluralism rooted in mutual respect, integration, and the shared principles of the European Convention on Human Rights.